Health promotion and prevention of cervical cancer: strategies used by nurses (Research, Society and Development, 2020)
Objective: to analyze the care carried out for the promotion of Health in the prevention of uterine cancer by nurses in Primary Health Care according to the Ministerial protocol. Methodology: a field research with a qualitative, descriptive and exploratory approach is specialized. The study was carried out with ten nurses linked to the Family Health Strategy Teams in a city in the Central Region of the State of Rio Grande do Sul. The selection occurs at random through a draw. Data collection was carried out through semi-structured interviews. The results obtained in the data collection were produced according to Minayo's content analysis. Results: three categories resulted. Health promotion as a nursing care strategy; Nursing care based on the Ministry of Health protocol; Access to services as a nursing care strategy. It is perceived that among nurses, care reveals a very heterogeneous work process, and the promotion and prevention of cervical cancer occurs in an uneven and fragmented way. Final considerations: for effective care as women, it is necessary that permanent health education be guided by changes, permeated with senses and meanings so that care is guided by scientific evidence and based on the official protocols instituted.